War and welfare : British POW families, 1939-45 - Hately-Broad, Barbara (Manchester University Press, 2009)
During the Second World War, some 250,000 British servicemen were taken captive by either the Axis powers or the Japanese. As a result of this, their families became completely dependent on the military & civil authorities. This book is essential reading for anyone interested in the British Home Front during the Second World War.